Wychowanie do ochrony przyrody w twórczości Drugiej Rzeczypospolitej - Wolter, Edyta (Biuletyn Historii Wychowania, 2012)
In the Second Republic of Poland, the education for the protection of nature was a part of an implicit didactic and educational process realized in primary and secondary schools – first of all as part of the education in natural science and geography (tourism). The kind of educational climate was created, connected with the establishment of protective care and sensibility for the natural environment, especially the indigenous nature. The article presents the analysis and interpretation of the printed sources, among others the publications by Maximilian Heilpern, Konrad Chmielewski, Hipolita Selmowiczówna-Gnoińska and Maria Lipska-Librachowa as well as Bronisław Gustawicz, Mieczysław Brzeziński, which were used in the didactic and educational practice in the period of the Second Republic of Poland in the process of shaping ecological attitudes. Many of them originated still in the years of Poland’s enslavement. They form valuable historical sources for studying, explaining and understanding the ecological education in the interwar period (1918–1939) – as an antecedence of the newest development trends in the educational theory and practice on ecology.